An unusual case of long-standing retained nasopharyngeal foreign body - Shafqat, Maimoona; Seema Naveed; Ambreen Riaz; Rabbani, Muhammad Zafar (Journal of the Pakistan Medical Association, 2024)
The nasopharynx is a rare anatomical location where a foreign body may become lodged after being ingested or inhaled. We are presenting a rare case of nasopharyngeal foreign body impaction in a two-and-a-half-year-old child that had been missed for almost a year. The child presented with a history of right-sided foul-smelling nasal discharge, snoring and mouth breathing. An X-Ray soft tissue lateral view of the post-nasal space showed an irregular partially radiopaque nasopharyngeal foreign body. The removal of the foreign body was performed under general anesthesia successfully. Foreign body impaction in the nasopharynx can easily be missed and it is important to keep this region in mind when dealing with missing inhaled or ingested foreign bodies. Keywords: nasopharynx, snoring, mouth breathing, radiopaque.